Meet the parents - Bently, Peter, 1960- (Simon & Schuster Books for Young Readers, 2014)
Although it sometimes seems that parents are just there to boss their children around, they are also good for many other things, from mending toys, kneecaps, and clothing to telling bedtime stories.